Supplementary Feeding as A Remedy For Stunted Toddlers and Pregnant Women With Chronic Energy Deficiency (CED) In Imbi Urban Village, Jayapura City, Papua - Ramadhanty, Syafierra (Pelopor Publikasi Akademika, 2024)
Stunting is a condition characterized by impaired growth in children, leading to insufficient height and weight compared to established standards, which also affects motor development. Children with stunting have lower immunity, increasing their vulnerability to non-communicable diseases such as diabetes, obesity, stroke, and heart disease. In Jayapura, the stunting rate reaches 20%, which is considered high in Indonesia. In response, PT Pertamina Patra Niaga has partnered with the Posyandu Cadre of Imbi Village and the local Health Center to provide Supplementary Feeding (PMT) containing animal protein, vegetable protein, fruits, and vegetables. The aim of this study is to evaluate the effectiveness of the PMT program in reducing the rate of stunting and improving the nutritional status of toddlers and pregnant women in Jayapura. The feeding program lasted for two weeks and targeted stunted children and pregnant women with nutritional deficiencies. This descriptive qualitative study examines the processes and outcomes of this intervention. The results indicate that 39% of participants successfully improved their nutritional status, moving out of the stunting and SEZ categories. This program is set to continue for four years to ensure sustainable support for toddlers and pregnant women in meeting their nutritional needs.